Management of anti-seizure medications in lactating women with epilepsy - Yan, Rong; Tuo, Jinmei; Tai, Zhenzhen; Zhang, Haiqing; Yang, Juan; Yu, Changyin; Xu, Zucai (Frontiers in Neurology, 2022)
Epilepsy is a common neurological disease. At present, there are about 70 million epilepsy patients in the world, half of them are women, and 30-40% of women with epilepsy are of reproductive age. Patients with epilepsy of reproductive age face more challenges than those with generalized epilepsy, such as seizures caused by hormonal fluctuations and the risk of adverse effects in mother and baby from taking anti-seizure medications (ASMs). Breast milk is one of the best gifts a mother can give her baby, it is nutritious, and breastfeeding will give more benefits to the baby. Compared with healthy people, people with epilepsy have more concerns about breastfeeding because they are worried that antiepileptic drugs in their milk will affect the growth and development of the baby, and they are always faced with the dilemma of whether to breastfeed after childbirth. So, whether female epilepsy patients can breastfeed while taking medication, and whether breastfeeding will adversely affect the baby, this article reviews the existing research on breastfeeding-related issues in female epilepsy patients, guides clinical practice, and improves the breastfeeding compliance of female epilepsy patients.